2009
DOI: 10.1097/ta.0b013e3181622bca
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Metastatic Fractures of the Femur: A Retrospective Analysis of 142 Patients

Abstract: Although many studies describe the endoprosthetic replacement as the safer method to treat pathologic femur fractures, our data showed that intramedullary stabilization and endoprosthetic replacement to be safe, and equivalent alternatives to treat complete pathologic fractures of the femur in patients with advanced metastatic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
82
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(95 citation statements)
references
References 22 publications
9
82
0
4
Order By: Relevance
“…Alternative treatments have been associated with dislocation, infection, nonunion, and disease progression, often requiring reoperation. Intraoperative complications such as hypotension, oxygen desaturation, embolization, and cardiac arrest have also been reported [2,9,12,22,24,[26][27][28]. Of note, Barwood et al [4] reported acute oxygen desaturation and hypertension in 11 of 45 patients treated with intramedullary nail fixation for metastatic tumors of the femur with actual or impending fractures.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Alternative treatments have been associated with dislocation, infection, nonunion, and disease progression, often requiring reoperation. Intraoperative complications such as hypotension, oxygen desaturation, embolization, and cardiac arrest have also been reported [2,9,12,22,24,[26][27][28]. Of note, Barwood et al [4] reported acute oxygen desaturation and hypertension in 11 of 45 patients treated with intramedullary nail fixation for metastatic tumors of the femur with actual or impending fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Hattori et al [11] reported a 1-year survival rate of 69%, although this represents only eight patients who underwent endoprosthetic reconstruction. Sarahrudi et al [28] reported a 1-year survival rate of 17% in a population in which 94 patients were treated with intramedullary nail fixation, 23 with endoprosthetic reconstruction, and 22 with open reduction and internal fixation. In this study, 76.7% of patients presented with multiple metastases at the time of fracture.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations